Pembelajaran Aransemen Musik Berbasis Teknologi Komputer di Jurusan Musik FSP Institut Seni Indonesia Yogyakarta - Tri Wahyu Widodo (PROMUSIKA, 2015)
Computer technology with its complex algorithms system made for a wide range benefits to support the efficiency of time and material of human labor. Because of that reason it has given a great contribution to the problem solving of human as its user, which commonly called the brain‐ware. Learning process is a human activity which is practiced on a daily basis. Various written and auditory obstacles faced by teachers and students. In music teaching, for example, a teacher gives examples by playing a musical instrument or through vocal practice. This activity is an example of manually teaching process that of course having some limitations. The purpose of this study is to provide an alternative in learning process that has interactive values. Computer technology will be contributed to make the learning process to be easier then mconventional way, for example, arranging or composing a piece of music in a form of large or small groups without requiring a huge cost. In order to fulfill musical creativity needs, current computer technology has been developing an intelligent electronic devices that can help users to access music menu application program by easily pressing buttons. Computer technology comprises unseparated parts of hardware and software due to their interrelated functions. The first as an electronic media while the second as a system for an operator person to command the computer in order to achieve his needs. This research has resulted an alternative formula in music learning‐teaching process by using computer technology, especially for several applied subjects such as arranging music and others theoretical subjects, for example music theory, harmony, counterpoint, and composition.